Child-Friendly Education Based on the Joyful Learning Approach in Elementary School Science and Social Studies Learning - Aziz Mukhamad Thoha; Fadhil Nur Hidayat; M. Ardian F.R. (Program Studi PGSD Universitas Madako Tolitoli, 2026)
The growing demand for child-friendly learning has become increasingly urgent, as elementary classroom practices remain largely oriented toward academic pressure and often fail to accommodate students’ psychological comfort. This condition contributes to low student engagement and limited confidence in expressing ideas. Therefore, this study aims to analyze the implementation of child-friendly education through a Joyful Learning approach in fourth-grade Science and Social Studies instruction at SDN Jerangkang, North Lampung. This study employed a qualitative approach with a case study design. The participants consisted of one fourth-grade teacher and five students. Data were collected through non-participant observation, semi-structured interviews, and documentation. Data were analyzed using thematic analysis, including open coding, categorization, and theme development to generate in-depth interpretations. The findings reveal that child-friendly education is reflected in the creation of a safe and comfortable learning environment, minimal pressure during instruction, and respect for students’ perspectives. The Joyful Learning approach was implemented through educational games, songs and movements, and contextual storytelling. These practices enhanced students’ active participation, conceptual understanding, self-confidence, and learning enthusiasm. This study highlights the importance of teachers’ creativity and pedagogical competence in fostering meaningful and enjoyable learning experiences.